Rappaport, Glisson, Hering, and Mall—Champions of Liver Microanatomy: Microscopic and Ultramicroscopic Anatomy of the Liver Into the Modern Age. (29th October 2021) - Gill, Ryan M.; Theise, Neil D.
Abstract :